Family law in Islam : divorce, marriage and women in the Muslim world - Voorhoeve, Maaike , 1979- (Library of Islamic law, 2012)
Using a range of contemporary examples, from polygamy to informal marriage (zawaj 'urfi), and from divorce with mutual agreement (khul') to judicial divorce (tatliq), this volume explores the impact of Islamic law on individuals, families and society alike from Morocco to Egypt and from Syria to Iran.